Programmed meiotic errors facilitate dichotomous sperm production in the silkworm, Bombyx mori - Leif Benner; Makenzie Richmond; Youbin Xiang; LingSze Lee; Clio B. Hockens; Tianwei Li; Zulin Yu; Dai Tsuchiya; Shengping Huang; Eelco C. Tromer; R. Scott Hawley; Leah F. Rosin (Proceedings of the National Academy of Sciences, 2026)
The goal of meiosis is typically to produce haploid gametes (eggs or sperm). Failure to do so is catastrophic for fertility. However, Lepidopteran (moths and butterflies) males produce two sperm morphs: nucleated (eupyrene) sperm and anucleated (apyrene) sperm, both of which are essential for fertilization. The meiotic differences in the two types of spermatogenesis are unclear, and our knowledge of the molecular differences between eupyrene and apyrene spermatogenesis is extremely limited in all systems. The only factor identified as being required for apyrene spermatogenesis is Sex-lethal ( Sxl ). Here, we show through cytological analysis of meiotic events that there are several key differences in the genesis of apyrene and eupyrene sperm. Specifically, during meiosis I, apyrene spermatocytes fail to decondense and pair their chromosomes during meiotic prophase I. Telomeres fail to localize to the nuclear periphery, and full-length synaptonemal complex does not form. We also find evidence of an abnormal second cell division during apyrene meiosis. RNA sequencing of both eupyrene- and apyrene-producing testes reveals distinct changes in transcriptional programs, including down-regulation of a myriad of cell division genes during apyrene meiosis. By comparing wildtype and Sxl -knockout apyrene testes, we found that Sxl is not required for regulating the expression of the cell division genes but instead may play a role in blocking hormone signaling from altering testis cell identity. Together, our findings reveal significant insights into two converging molecular pathways that promote the formation of dimorphic sperm in Lepidoptera.